Peran Media Pembelajaran Matematika sebagai Teknologi dan Solusi dalam Pendidikan Di Era Digitalisasi dan Disruption - Nursiya Bito; Abd. Kadim Masaong (Jambura Journal of Mathematics Education, 2023)
Technology makes a very important contribution to mathematics learning. The main requirement for successful integration of technology in learning mathematics is about willingness and commitment to adapt to change through learning design activities by preparing the right learning tools and resources, including media. This study aims to determine the effectiveness of integrating media in mathematics learning in Grade VII of SMP Negeri 11 Gorontalo. The method used is descriptive which examines the teacher's ability to manage learning, student learning activities, responses, and learning outcomes. Based on the descriptive analysis of the results of research on the effectiveness of mathematics learning media as educational technology at SMP Negeri 11 Gorontalo with indicators of the teacher's ability to manage learning, student learning activities, student responses and classical learning outcomes it can be concluded that the teacher's ability to manage learning is categorized as effective, student activity is categorized effective, student responses to learning activities is positive, and classically complete learning outcomes. Thus, the integration of media in learning mathematics in Grade VII of SMP Negeri 11 Gorontalo can be said to be effective.